2019
DOI: 10.1158/1078-0432.ccr-18-1955
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Transcriptomics of Pancreatic Cancer Precursors Demonstrates Epithelial and Microenvironmental Heterogeneity as an Early Event in Neoplastic Progression

Abstract: Purpose: Early detection of pancreatic ductal adenocarcinoma (PDAC) remains elusive. Precursor lesions of PDAC, specifically intraductal papillary mucinous neoplasms (IPMNs), represent a bona fide pathway to invasive neoplasia, although the molecular correlates of progression remain to be fully elucidated. Single-cell transcriptomics provides a unique avenue for dissecting both the epithelial and microenvironmental heterogeneities that accompany multistep progression from noninvasive IPMNs to PDAC. Experimenta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
284
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 294 publications
(301 citation statements)
references
References 72 publications
17
284
0
Order By: Relevance
“…Interestingly, Bernard et al demonstrated that microenvironmental heterogeneity occurs in premalignancy and throughout cancer progression [61]. This study examined iCAF and myCAF populations in PDAC and in precursor low-grade and high-grade intraductal papillary mucinous neoplasms (LG-and HG-IPMN) [61].…”
Section: Caf Heterogeneity Based On Spatial Locationmentioning
confidence: 95%
See 1 more Smart Citation
“…Interestingly, Bernard et al demonstrated that microenvironmental heterogeneity occurs in premalignancy and throughout cancer progression [61]. This study examined iCAF and myCAF populations in PDAC and in precursor low-grade and high-grade intraductal papillary mucinous neoplasms (LG-and HG-IPMN) [61].…”
Section: Caf Heterogeneity Based On Spatial Locationmentioning
confidence: 95%
“…iCAFs were only apparent in PDAC, whereas myCAFs were lowly abundant in LG-IPMN and highly abundant in HG-IPMN, indicating that myCAF activation can also occur in the non-invasive setting. Interestingly, the increase in iCAFs coincided with a clearly defined switch from immunosurveillance (LG-IPMN) to immunosuppression (PDAC) [61]. Considering that iCAFs produce high levels of chemokines and cytokines that are involved in tumourigenesis and disease progression, it is likely that these cells are also responsible for aggressive tumour spread, although this correlation has yet to be explicitly elucidated.…”
Section: Caf Heterogeneity Based On Spatial Locationmentioning
confidence: 99%
“…Similarly, solid cancers can alter the metastatic niche even before colonization (Kaplan et al, 2005; Costa-Silva et al, 2015; Olmeda et al, 2017). Single-cell sequencing of primary human breast, lung, and pancreatic cancers has revealed heterogeneity not only in the cancer populations but also in immune and other cells of the microenvironment (Bartoschek et al, 2018; Bernard et al, 2019; Elyada et al, 2019; Lawson et al, 2018; Ma et al, 2019; Wagner et al, 2019). Defining the spatial localization of CSCs with respect to specific niche cells, and understanding how these interactions contribute to cancer progression and response to therapy, will be exciting future avenues of work.…”
Section: Future Directionsmentioning
confidence: 99%
“…Importantly, the presence of iCAF and myCAF populations in human PDAC Cancer Research. in vivo has been recently confirmed (20). However, the signals that drive the formation of these distinct populations are not known.…”
Section: Introductionmentioning
confidence: 98%